Area Minat Literatur Ilmiah Perawat di Dua Rumah Sakit di Kota Depok: Survei Konten Mobile Application - Melati Fajarini; Sri Rahayu (Jurnal Persada Husada Indonesia, 2019)
Knowledge transfer by disseminating scientific literature (evidence) of nurses in Depok through a mobile application is potential. However, the area of interest in the evidence is unknown. This study aims to identify areas of interest in evidence as a recommendation for the mobile application content. This demographic questionnaire was completed online by 110 nurses in two public and private public hospitals in Depok City in August and September 2019. Descriptive analysis showed nurses were interested in Surgical Medical Nursing (47.3%), Nursing Management (24.5%), Child Nursing (11.8%) and Emergency Nursing (10.9%). The content of evidence in mobile applications for nurses in hospitals needs to prioritize these areas of interest.